EFFECT OF YOGA ON DEPRESSION AND QUALITY OF LIFE IN DRUG ABUSERS (International Journal of Ayurveda and Pharma Research, 2015)
Background: Drug abuse including alcohol may lead to health problems, social problems, morbidity, injuries, unprotected sex, violence, deaths, motor vehicle accidents, homicides, suicides, physical dependence or psychological addiction. Objectives: To study the efficacy of yoga on Quality of life of drug abusers and to study the efficacy of Yoga on measures of depression of drug abusers. Methods and Materials: 66 drug abused males with the mean age of 32.50±9.86 years participated in the randomized control trial pre and post study. BDI-II and WHOQOL-BREF were used to assess depression score and quality of life before and after. Statistical analysis: Shapiro - Wilk, Wilcoxon signed rank test and Mann Whitney test were used for analyzing the data with the help of SPSS 16. Results: There was significant reduction after yoga intervention in depression scores (BDI-II) (p=0.000) and significant increase in Quality of life Domain 1, 2 and 3 (p=0.000, p=0.043, p=0.015). There was no significant increase in QOL Domain 4 (p=0.089). Regarding wait list control group, after the intervention programme, there was significant reduction in depression score, (p=0.040) and no significant increase in QOLBREF score in all four domains. Conclusion: Thus this study has shown that Yoga practice can help in reducing depression symptoms and increased quality of life in drug abuser.